Some Characterization of Fermatean Fuzzy L-ring Ideals - Adak, Amal Kumar; Kamal, Nil; Ali, Wajid (Soft Computing Fusion with Applications, 2024)
The Fermatean fuzzy set (FFS) represents a robust approach for addressing ambiguity, effectively managing issues that remain unresolved by Intuitionistic fuzzy set and Pythagorean fuzzy set concepts. Due to its practical utility and significant impact on tackling real-world challenges across various domains, FFS has spurred extensive research. This study defines Fermatean fuzzy sublattice and Fermatean fuzzy lattice. Additionally, it introduces Fermatean fuzzy L-ring ideals. The paper explores the concept of homomorphism within Fermatean fuzzy sets. Furthermore, it investigates important findings concerning the image and pre-image of Fermatean fuzzy L-ring ideals, utilizing properties of infimum and supremum. The results are illustrated through pertinent numerical examples.